Long-Term Field Studies of Primates - Kappeler, Peter M.; Watts, David P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Some primate field studies have been on-going for decades, covering significant portions of individual life cycles or even multiple generations. In this volume, leading field workers report on the history and infrastructure of their projects in Madagascar, Africa, Asia and South America. More importantly, they provide summaries of their long-term research efforts on primate behaviour, ecology and life history, highlighting insights that were only possible because of the long-term nature of the study. The chapters of this volume collectively outline the many scientific reasons for studying primate behaviour, ecology and demography over multiple generations. This kind of research is typically necessitated by the relatively slow life histories of primates. Moreover, a complete understanding of social organization and behaviour, factors often influenced by rare but important events, requires long-term data collection. Finally, long-term field projects are also becoming increasingly important foci of local conservation activities.
Part I Introduction -- The Values and Challenges of Long-Term Field Studies -- Part II Madagascar -- Berenty Reserve, Madagascar: A Long Time in a Small Space -- Beza Mahafaly Special Reserve: Long-Term Research on Lemurs in Southwestern Madagascar -- Long-Term Lemur Research at Centre Valbio, Ranomafana National Park, Madagascar -- A 15-Year Perspective on the Social Organization and Life History of Sifaka in Kirindy Forest -- Part III America -- The Northern Muriqui (Brachyteles hypoxanthus): Lessons on Behavioral Plasticity and Population Dynamics from a Critically Endangered Species -- The Lomas Barbudal Monkey Project: Two Decades of Research on Cebus capucinus -- Tracking Neotropical Monkeys in Santa Rosa: Lessons from a Regenerating Costa Rican Dry Forest -- The Group Life Cycle and Demography of Brown Capuchin Monkeys (Cebus [apella] nigritus) in Iguazú National Park, Argentina -- Part IV Asia -- Social Organization and Male Residence Pattern in Phayre's Leaf Monkeys -- White-Handed Gibbons of Khao Yai: Social Flexibility, Complex Reproductive Strategies, and a Slow Life History -- V Africa -- The Amboseli Baboon Research Project: Forty Years of Continuity and Change -- The Thirty Year Blues: What We Know and Don t Know About Life History, Group Size, and Group Fission of Blue Monkeys in the Kakamega Forest, Kenya -- Long-Term Research on Chimpanzee Behavioral Ecology in Kibale National Park, Uganda -- Long-Term Field Studies of Chimpanzees at Mahale Mountains National Park, Tanzania -- Long-Term Studies of the Chimpanzees of Gombe National Park, Tanzania -- Long-Term Research on Grauer s Gorillas in Kahuzi-Biega National Park, DRC: Life History, Foraging Strategies, and Ecological Differentiation from Sympatric Chimpanzees -- Long-Term Studies on Wild Bonobos at Wamba, Luo Scientific Reserve, D.R. Congo: Towards the Understanding of Female Life History in a Male-Philopatric Species. VI Summary -- A Comparative Perspective on Long-term Field Studies.
Keywords: Life sciences; Animal behavior; Animal ecology; Conservation biology; Evolution (Biology).; Life Sciences; Behavioural Sciences; Animal Ecology; Evolutionary Biology; Conservation Biology/Ecology.